Judith Butler : from norms to politics - Lloyd, Moya (Polity Press, 2007)
With the publication of her highly acclaimed and much-cited book Gender Trouble, Judith Butler became one of the most influential feminist theorists of her generation. Her theory of gender performativity and her writings on corporeality, on the injurious capacity of language, on the vulnerability of human life to violence and on the impact of mourning on politics have, taken together, comprised a substantial and highly original body of work that has a wide and truly cross-disciplinary appeal. In this lively book, Moya Lloyd provides both a clear exposition and an original critique of Butler's work. She examines Butlers core ideas, traces the development of her thought from her first book to her most recent work, and assesses Butlers engagements with the philosophies of Hegel, Foucault, Derrida, Irigaray and de Beauvoir, as well as addressing the nature and impact of Butler's writing on feminist theory. Throughout Lloyd is particularly concerned to examine Butler's political theory, including her critical interventions in such contemporary political controversies as those surrounding gay marriage, hate-speech, human rights, and September 11 and its aftermath. Judith Butler offers an accessible and original contribution to existing debates that will be an invaluable resource for students and scholars alike.